JAPAN AS A PLAN RATIONAL AND DEVELOPMENTAL STATE: THE GOVERNMENT’S ROLE IN HIGH SPEED GROWTH OF ECONOMY IN THE POSTWAR PERIOD - MUJTAHID SUBAGYO (Universitas Negeri Yogyakarta, 2005)
Japan as a Plan Rational and Developmental State: The Government’s Role in High Speed Growth of Economy in the Postwar PeriodJapanese high speed economic growth, which many of them called it as a miracle or in Japanese term as jukagaku kogyoka, is affected by many factors. Many economists tried to find out the rationale behind this high speed growth. Some of their analysis can be categorized as national character/factor of culture analysis, no-miracle-occurred analysis, unique structural feature analysis, and free ride analysis. To explain the concept of plan rational, it needs to compare to such other concept as the market rational system. Basically the difference between these two concepts is on the function of state in the macro and micro economic policies. On the other hand, the countries which experienced the late industrialization process, the state played the significant role as the driver of the process itself. Thus it has the role of developmental functions. These two different approaches used by two types of countries (Japan and USA) caused the different effect in the states and private sector’s relationship. The differences between these two types of states are focused on the trade regulations, efficiency and effectiveness, structure of domestic industry, and, the institution of decision making. Keywords : Government Role, Economic Growth, Japan